Interwar Europeanism: A step towards integration? The Briand Memorandum and the Commission for the Study of a European Union - Ramiro Troitiño, David (Cuadernos de Historia Contemporánea, 2022)
Aristide Briand in 1929 before the Assembly of the League of Nations in Geneva, called for a union of Europe through reconciliation and peace, institutionally initiating a very ambitious process in its scope, its objectives and its possibilities. However, numerous difficulties bogged down the development of this project. This research focuses, thanks to the recently digital archives of the League of Nations, on Aristide Briand's proposal on the United States of Europe. The project was not properly European, nor federal, it count with the opposition from Great Britain and did not include in its design any integration between Member States. These events, in addition to the economic crisis and the political situation in Europe, destroyed the early European dream and the idea of continental peace that later triumphed with the European Communities.
Keywords: Integration; European Union; history of European integration; Aristide Briand; League of Nations; peace